Interest Dispute Settlement Related to Workers’ Health Care Security in Indonesia - Dewa Nyoman Rai Asmara Putra; Kadek Agus Sudiarawan; Ari Mahartha (Udayana Journal of Law and Culture, 2020)
The enactment of Law Number 24 of 2011 concerning the Social Security Organizing Body (BPJS Law) has legal implications especially for employers and workers before the enactment of the BPJS Law, the Parties had already agreed that Private Health Insurance as an organizer of workers' health insurance on Collective Labor Agreement (CLA). This condition provides a possibility for the emergence of conflicts of interest. The problem raised in this legal research is how is the regulation concerning the employers' obligations in the health insurance of workers after the enactment of the BPJS Law; what are the legal implications if the CLA in the company before the enactment of BPJS Law has implemented the scheme of Health Insurance for Workers through Private Insurance; and how the legal steps that can be taken in resolving disputes arising related to this matter. This study uses normative legal research methods with a statute approach and a case approach. The result of this research shows that after the enactment of BPJS law, the Employer is obliged to register all of the Workers to BPJS membership as the national provider of health care security system. In terms of double coverage of Workers’ health insurance which impacted the company, the parties could negotiate to amend the CLA based on mutual agreement and good faith. In terms of an interest dispute in implementing the CLA about workers’ health insurance is happening in the future, legal actions that can be taken accordance with the provisions of the Industrial Relations Disputes Settlement Law are bipartite, tripartite disputes settlement through mediation, conciliation, arbitration, and submit a lawsuit to Industrial Relations Court